Milk MicroRNAs in Health and Disease. Issue 3 (10th March 2019) - Benmoussa, Abderrahim; Provost, Patrick
Abstract: MicroRNAs are small noncoding RNAs responsible for regulating 40% to 60% of gene expression at the posttranscriptional level. The discovery of circulating microRNAs in several biological fluids opened the path for their study as biomarkers and long‐range cell‐to‐cell communication mediators. Their transfer between individuals in the case of blood transfusion, for example, and their high enrichment in milk have sparked the interest for microRNA transfer through diet, especially from mothers to infants during breastfeeding. The extension of such paradigm led to the study of milk microRNAs in the case of cow or goat milk consumption in adults. Here we provide a comprehensive critical review of the key findings surrounding milk microRNAs in human, cow, and goat milk among other species. We discuss the data on their biological properties, their use as disease biomarkers, their transfer between individuals or species, and their putative or verified functions in health and disease of infants and adult consumers. This work is based on all the literature available and integrates all the results, theories, debates, and validation studies available so far on milk microRNAs and related areas of investigations. We critically discuss the limitations and outline future aspects and avenues to explore in this rapidly growing field of research that could impact public health through infant milk formulations or new therapies. We hope that this comprehensive review of the literature will provide insight for all teams investigating milk RNAs' biological activities and help ensure the quality of future reports.